Gambaran Pengetahuan Keluarga Tentang Latihan Fisik Pada Pasien Diabetes Mellitus di Puskesmas Juwana Pati - Devi Setya Putri; Septika Faulia; Alvi Ratna Yuliana; Nila Putri Purwandari; Luluk Cahyanti (Lembaga Pengembangan Kinerja Dosen, 2024)
Diabetes mellitus (DM) is a disorder of carbohydrate, protein and fat metabolism characterized by hyperglycemia or increased blood glucose levels that occur as a result of abnormal insulin secretion or decreased insulin action (Buraerah, 2015). The DM management includes 4 main pillars, one of which is physical exercise. Physical exercise is one of the pillars in the management of DM which functions to improve insulin sensitivity and also to maintain a healthy body (Mala, 2018). However, when sufferers don’t go through this management, this is where the role of the family is as a support (Waspadji, 2014). To find out the description of family knowledge about physical exercise in diabetes mellitus patients at the Juwana Pati Healty Center. The type of research used is quantitative research using descriptive studies. The number of samples in this study were 55 respondents with a total sampling technique. The results showed that the family's knowledge of physical exercise in patients with diabetes mellitus was mostly female, 35 respondents (63.6%), housewife job level was 28 respondents (50.9%), high school education level was 16 respondents (29, 1%), the level of moderate physical exercise is 26 respondents (47.3), the level of sufficient family knowledge is 19 respondents (34.5%), and vulnerable aged 47-57 years as many as 22 respondents (40.0%). That most of the family's knowledge about physical exercise in patients with diabetes mellitus has sufficient knowledge as many as 19 respondents (34.5%).